2017
DOI: 10.3892/ol.2017.7227
|View full text |Cite
|
Sign up to set email alerts
|

In�vivo and in�vitro induction of the apoptotic effects of oxysophoridine on colorectal cancer cells via the Bcl‑2/Bax/caspase-3 signaling pathway

Abstract: Oxysophoridine (OSR) is a major active alkaloid extracted from Sophoraalopecuroides L. The aim of the present study was to investigate the induction of the apoptotic effects of OSR on colorectal cancer cells in vivo and in vitro. The results of the MTT and colony formation assays demonstrated that the proliferation of HCT116 cells was inhibited by OSR in vitro. The characteristics of cellular apoptosis in OSR-treated HCT116 cells were analyzed by Hoechst 33258 staining. It was also observed that the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Ahmed & El Menoufy [45] and Farhadi et al [6], approved these mechanisms in executing tumor cells in vitro in human colon cancer cells and in human oral squamous cell carcinoma respectively. Also, our data are in accordance with Jin et al [46] who denoted a significant apoptotic effect on colorectal cancer cells in vitro and in vivo which was accompanied with the Bcl-2/Bax/caspase-3 signaling pathway. These observations were confirmed by the experiment applied by Russo et al [47] who approved these apoptotic mechanisms in human prostate cancer cells in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…Ahmed & El Menoufy [45] and Farhadi et al [6], approved these mechanisms in executing tumor cells in vitro in human colon cancer cells and in human oral squamous cell carcinoma respectively. Also, our data are in accordance with Jin et al [46] who denoted a significant apoptotic effect on colorectal cancer cells in vitro and in vivo which was accompanied with the Bcl-2/Bax/caspase-3 signaling pathway. These observations were confirmed by the experiment applied by Russo et al [47] who approved these apoptotic mechanisms in human prostate cancer cells in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…11 The caspases and Bcl-2 family of proteins (antiapoptotic and pro-apoptotic proteins) are recognized as the main regulators of the apoptotic pathway. 43 Bax translocation into mitochondria could change the cytochrome C permeability, followed by stimulation of the post-mitochondrial caspase, leading to apoptotic cell death. 43 Bcl-2 prevents cell apoptosis by decreasing the release of cytochrome C in order to suppress caspase-3 activation.…”
Section: Discussionmentioning
confidence: 99%
“…43 Bax translocation into mitochondria could change the cytochrome C permeability, followed by stimulation of the post-mitochondrial caspase, leading to apoptotic cell death. 43 Bcl-2 prevents cell apoptosis by decreasing the release of cytochrome C in order to suppress caspase-3 activation. 44 Intrinsic and extrinsic pathways are two main routes of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase‐3 was the main terminal shear enzyme in the process of cell apoptosis. When the intracellular Bax/Bax homodimer increases, Caspase‐3 could be activated and transform into Cleaved‐caspase‐3, then to trigger the downstream cascade reaction, destroy the integrity of DNA and lead to cell apoptosis (Wang, Zhang, Wang, Song, & Yuan, ; Cong et al., ; Jin et al., ; Safhi, ). In this study, we found that GMP‐Na 2 (250 mg/kg) could down‐regulated the expressions of Caspase‐3, Bax mRNA and protein in liver tissue of mice with AHI, and upregulated the expression of Bcl‐2.…”
Section: Discussionmentioning
confidence: 99%